Avaliação de membrana de tubogotejador em função do teor de ferro na água - Brauer, Rigléia Lima [UNESP] (2014)
The objective of this study was to evaluate the wear of self-compensating dripline as a functional of membrane water rich in iron, an experiment was conducted in the experimental area of the Departament of Rural Engineering, Universidade Estadual Paulista Julio de Mesquita Filho - Faculty of Agricultural Sciences, located in Botucatu - SP by the geographical coordinates 22º 49' and 48°25'W, height 770 m . The test match wear membranes self-compensating dripline, and was rated the dripper NaanPC company NaanDanJain blue. The experiment was a factorial 2x13 scheme, two doses of 13 Fe and run times with three replicates, totaling 78 experimental plots. To conduct the test, were drawn from a coil at random segments of 18 to 35 meters in average emitter 44 dripline for each row of drippers. which resulted in the evaluation of a total o 396 drippers for each treatment. The working pressure was maintained at 150+-15KPa. The water used in used in the assay were from the Lake of the Rural Engineering Department which is commonly used for irrigation experiments. Subsequently were calculated: Flow, Flow Coefficient of Variation (CVQ), Uniformity of Water Distribution (CUD) and relative density (Dr). The results showed no significant difference in any of the treatments at different of iron.